Aging With Intellectual Disabilities in Families: Navigating Ever-Changing Seas—A Theoretical Model. (September 2019) - Trip, Henrietta; Whitehead, Lisa; Crowe, Marie; Mirfin-Veitch, Brigit; Daffue, Chris
Life expectancy is increasing for people with intellectual disability, many of whom live with family. While there has been research about aging and future planning, there is limited evidence about the characteristics of the caregiving relationship. The aim of this study was to examine perspectives of caregiving for older people with intellectual disability and their family. A constructivist grounded theory approach was used, and 19 people with intellectual disability and 28 family members were interviewed. Caregiving was informed by transitions across the life course. Three interrelated concepts, Riding the Waves, Shifting Sands—Changing Tides, and Uncovering Horizons comprise the core components of the theoretical model— Navigating Ever-Changing Seas. This model informs complex, trans-generational relationships that impact decision-making for people with a long-term condition. Applications within health care indicate a need for systems to include individuals and their networks of care in policy, practice, research, and service delivery across the lifespan.